Dinamika Penanganan Pelanggaran Administrasi: Studi Terhadap Kepatuhan Putusan Dan Rekomendasi Bawaslu Terkait Pelanggaran Administrasi Pemilu/Pilkada - Supriyadi Supriyadi; Widyatmi Anandy (Badan Pengawas Pemilihan Umum, 2020)
Bawaslu is an institution that is given the authority to resolve election / election administration violations. The nature of Bawaslu's decisions and recommendations for administrative violations must be followed up by the KPU and its officials, this is confirmed in the provisions of Article 462 of Law No. the administration issued by Bawaslu is not obeyed by the institution implementing the decision / recommendation. Identification of problems: first, what is the nature of mandatory norms in the provisions of the Election / Pilkada Law? Related to follow-up on decisions / recommendations of Bawaslu Administrative Violations? Second, how is the Compliance with the Decision / Recommendation of Administrative Violation of Bawaslu? Third, what factors influence compliance with Bawaslu Administrative Violation Decisions / Recommendations? This research is a normative juridical study with a focus on analyzing decisions / recommendations for administrative violations of Bawaslu. in this study using a statutory approach, a case approach, and a conceptual approach. The data sources used are primary, secondary and tertiary data. The research results and conclusions. First, the